1988
DOI: 10.1002/ddr.430140310
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter clinical placebo‐controlled study with acetyl‐l‐carnitine (LAC) in the treatment of mildly demented elderly patients

Abstract: Acetyl-I-carnitine (LAC) was administered for 3 months, 2 gidaily, to 30 elderly patients with mild mental deterioration. Results were compared to those of a homogeneous control group of 28 patients treated with placebo. The study was carried out according to a double-blind, randomized methodology. A complete battery of rating scales and psychometric tests was used for for evaluating the modifications induced by either drug or placebo. The statistical evaluation of results showed a sufficient clear efficacy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…ST200 was chosen as the reference drug since consistent evidence exists about its efficacy in improving cognitive functions in SDAT (Calvani & Carta 1991;Cucinotta et al 1988;Parnetti et al 1990;Rai et al 1990). …”
Section: Discussionmentioning
confidence: 99%
“…ST200 was chosen as the reference drug since consistent evidence exists about its efficacy in improving cognitive functions in SDAT (Calvani & Carta 1991;Cucinotta et al 1988;Parnetti et al 1990;Rai et al 1990). …”
Section: Discussionmentioning
confidence: 99%
“…34 Similarly, N-acetyl-carnitine may improve cognitive function and memory in people with age-related cognitive decline and memory impairment. 35 Much research has been done, using this compound, to help people with Alzheimer's disease, which is marked by a significant decrease in acetylcholine and cholinergic neurons. 36…”
Section: Neurologic Functionmentioning
confidence: 99%
“…Placebo-controlled trials have shown the efficacy of ALC in improving the cognitive performance of patients suffering from senile dementia of Alzheimer type (SDAT) [11,12]. When looking at the pathogenetic as pects of the disease, emphasis is nowadays put on neu roendocrine alterations, and particularly on the dysregulation of the hypothalamus-pituitary-adrenal (HPA) axis, a common finding in Alzheimer's disease [13].…”
Section: Introductionmentioning
confidence: 99%